V-ATPase V(0) Sector Subunit a1 in Neurons Is a Target of Calmodulin(,) - Zhang, Wei (J Biol Chem, 2007)
The V(0) complex forms the proteolipid pore of a vesicular ATPase that acidifies vesicles. In addition, an independent function in membrane fusion has been suggested in vacuolar fusion in yeast and synaptic vesicle exocytosis in fly neurons. Evidence for a direct role in secretion has also recently been presented in mouse and worm. The molecular mechanisms of how the V(0) components might act or are regulated are largely unknown. Here we report the identification and characterization of a calmodulin-binding site in the large cytosolic N-terminal region of the Drosophila protein V100, the neuron-specific V(0) subunit a1. V100 forms a tight complex with calmodulin in a Ca(2+)-dependent manner. Mutations in the calmodulin-binding site in Drosophila lead to a loss of calmodulin recruitment to synapses. Neuronal expression of a calmodulin-binding deficient V100 uncovers an incomplete rescue at low levels and cellular toxicity at high levels. Our results suggest a vesicular ATPase V(0)-dependent function of calmodulin at synapses.